Comparison of plant species communities in meadows of the nature reserve "Bodenmöser" from 1987 to 2014 - Viebranz, Katharina (SLU/Dept. of Aquatic Sciences and Assessment, 2015)
This master thesis compares plant species communities which were conducted within the same area at thre different times. The study area of this thesis is located in the southeast of the German federal state of Baden-Württemberg close to the town Isny im Allgäu. For a period of over 700 years the meadows in this region were traditionally used as water meadows. Water meadows are a traditional agricultural practice where meadows are irrigated in early spring every year to unfreeze the soil, start the vegetation growth earlier and to fertilize them. This practice was stopped in the middle of the last century. In 1990 large parts of the study area, together with surrounding mires and other types of wetlands, were declared a nature reserve. It is one of the last large contiguous areas in Baden-Württemberg where different stages of mire development and wetland habitats exist next to each other. Of special interest for this thesis are the different types of meadows in the eastern parts of the nature reserve “Bodenmöser”. It is suspected that the plant species diversity of the meadows has decreased and the plants species composition has markedly changed since 1989. Since the declaration as a nature reserve in 1990 until today several experts in ecology increasingly suspected that the plant species diversity in the former water meadows had been reduced. It was observed that some plant species seem to have become dominant and to have superseded others. This of course would counteract the aim of the nature reserve, which is the conservation of nature. The focus of this master thesis will be to investigate whether this is the case and if so, what could possible reasons for those changes be. Therefore two data sets from previous plant species inventories (1987 and 1997) are compared with a new data form spring/summer 2014. The field mapping of this data set was part of this master thesis. The analyses of the three data sets show temporal trends in the plant species composition. Changes in local conditions were assessed using Ellenberg’s indicator values and available data on management. The results show that soil moisture and nutrient content of the soil has the biggest influence on the distribution of plant species in the study area. Both were proven to be big explanatory factors for the plant species composition. Also it was confirmed that the species composition has changed over the years. Especially the loss of several endangered species was alarming. It was concluded that the current management measures need to be evaluated, revised and adjusted. The partial restoration of the water meadow system could help to restore wetter soil conditions to support the adapted plant species composition. At the same time the nutrient input on some biotopes should be reduced to lower productivity and raise biodiversity.